Progress in Research on the Role of FGF in the Formation and Treatment of Corneal Neovascularization - Chen, Mengji; Bao, Licheng; Zhao, Mengying; Cao, Jiarong; Zheng, Haihua (Frontiers in Pharmacology, 2020)
Corneal neovascularization (CNV) is a sight-threatening disease usually associated with inflammatory, infectious, degenerative, and traumatic disorders of the ocular surface. Fibroblast growth factor (FGF) family members play an important role in angiogenesis to induce corneal neovascularization, which significantly affects the differentiation, proliferation, metastasis, and chemotaxis of vascular endothelial cells. Both acidic fibroblast growth factor (aFGF) and basic fibroblast growth factor (bFGF) demonstrate positive staining in capillaries and induce corneal stromal cells. The anabolism of endothelial cells is induced by bFGF in corneal neovascularization. FGFs exert their effects via specific binding to cell surface-expressed specific receptors. We believe that both anti-FGF antibodies and anti-FGF receptor antibodies represent new directions for the treatment of CNV. Similar to anti-vascular endothelial growth factor antibodies, subconjunctival injection and eye drops can be considered effective forms of drug delivery.